Identificando valores de referência para predição de sucesso e fracasso em open source software: um estudo empírico - Fortunato, Diogo Vieira (2011)
Faced with a context where much of the open source projects are considered failure this study investigated reference values for metric sin the literature and metrics from Apache JIRA Issue Tracker for these metric scan be used as reference to infer the state of OSS project (Open Source Software). By calculating the mean and standard deviation of the values found, Bayesian networks were trained to check if these values were valid. This study also examines some metrics proposed by Principal Component Analysis (PCA)in order to investigate the correlations between these metrics.